Proteome changes during in vitro culture adaptation of Toxoplasma gondii archetypal II and III field isolates - Müller, Joachim; Regidor-Cerrillo, Javier; Arranz-Solís, David; Braga-Lagache, Sophie; Uldry, Anne-Christine; Heller, Manfred; Calero-Bernal, Rafael; Hemphill, Andrew; Ortega-Mora, Luis Miguel (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionRapid in vitro culture adaptation of recently obtained Toxoplasma gondii isolates leading to deep changes in relevant phenotypic traits has been demonstrated earlier. Few reports exist on the molecular bases that govern this adaptation. Herein, we analyzed the T. gondii proteomes of different isolates at two timepoints during cell culture adaptation.MethodsThe differential proteomes of six recently obtained archetypal European T. gondii Type II (TgShSp1 (Genotype ToxoDB#3), TgShSp2 (#1), TgShSp3 (#3) and TgShSp16 (#3)) and Type III (TgShSp24 (#2) and TgPigSp1(#2)) isolates maintained at low (10-16) and high (50-53) passage numbers in Vero cells were determined by label free liquid chromatography–mass spectrometry.ResultsAmong these isolates, 2.3% and 10.2% of proteins were differentially or constantly abundant when comparing low and high passage numbers. Constant proteins included components involved in essential cellular processes such as energy metabolism or protein synthesis, many of them identified as drug and vaccine targets. Interestingly, differentially abundant proteins were clearly linked to phenotypic changes associated to in vitro adaptation: loss of ability to spontaneously form cysts at high passages and decreased expression of cyst and bradyzoite markers (BAG1, Enolase 1, and SRS35A), while culture adaptation was associated with increased abundance of recognized virulence factors such as GRA15, GRA16, TEEGR and NSM.ConclusionOur results highlight the changes at the proteomic level that take place in recently obtained isolates after in vitro culture adaptation, an important feature that should be considered during T. gondii investigations.